Graphene monolayers and nanoribbons with controlled domain sizes of hexagonal boron nitride: An ab initio calculations. (February 2019) - Guerra, T.; Leite, L.; Azevedo, S.
Abstract: Boron nitride (BN) doped graphene (G), has been synthesized recently and shown to be an efficient method to engineer energy gaps in graphene. The control of the dopant domain size allows us to tailor the structural, electronic and optical properties of the graphene. Here, we have used first-principles calculations based on the density functional theory (DFT) to investigate the structural, magnetic, electronic and optical properties of graphene monolayers and nanoribbons with different (BN) concentrations. Our results show that the formation energy these systems can increases or decreases with the doping. Interfacial energy in these systems plays an important role. The lowest formation energies were found for the systems that present the smallest variations in the bond lengths. G/BN heterostructures display a value for energy gap, which is tunable and varies almost linearly with the BN concentration. Based on the analysis of the imaginary part of the dielectric function, it is found that such hybrids nanostructures, present potential applications in optical devices. Highlights: From of the optical properties is possible to verify the absorption in visible region. The value for energy gap, varies almost linearly with BN concentration. Such structures, present potential applications in optical devices.